As religiões afro-brasileiras na educação: desafios com a lei 10.639/03 nas escolas públicas na rede municipal do Recife. - Oliveira, Josilene Bezerra de (2020)
The research aimed to understand Law 10.639/03 in the school curriculum of Public Schools of Recife Municipal Network, contextualizing its practices of teaching and learning regarding the religions of African Matrix. We reflected on the practice of religious education and the obligation to teach Afro-Brazilian and African History and culture in public and private schools from elementary to high school. This is a qualitative study, with the use of bibliographical, documentary and semi structured interviews. The research had support in the idea of social transformation. We noticed that the Public Schools of the Municipal Network of Recife have a practice of pedagogical reflection on Law 10.639/03. A series of measures were adopted to assure the resignification of the school curriculum and the sessions for the knowledge of the history of Africa and the Afro-Brazilian scenery. However, most of the students of Recife's Municipal Teaching Network practiced popular Protestantism, a fact that made it difficult to implement the Law, since many came to their churches with a pre-conceived view of the religions of the African matrix. On the other hand, it should be noted that many teachers are unaware of the Law and the understanding of Afro-Brazilian history and culture in schools. Those who know it are the ones who are most present and included in the continuing formation offered by the Municipal Network of Teaching or are engaged in political movements.